Comparative Efficacy of Serum Creatinine and Microalbuminuria in Detecting Early Renal Injury in Asphyxiated Babies in Calabar, Nigeria - Ochigbo, Sunday O.; Jacob, Udo J.; Nlemadim, Anthony C.; Kudirat, Olaniyo O. (International Journal of Child Health and Nutrition, 2016)
Background: Microalbuminuria and serum creatinine are markers of acute kidney injury. Birth asphyxia is responsible for 50% of all newborn deaths and acute non-oliguric kidney injury is one of such complications. This study was undertaken to determine the efficacy of serum creatinine and microalbuminuria for the detection of early renal lesion in severely asphyxiated babies in Calabar, Nigeria. Materials and Method: This prospective cross-sectional investigational study was undertaken among severely asphyxiated babies admitted into the newborn units of the University of Calabar Teaching Hospital (UCTH), Calabar, Nigeria. Standard method for blood collection and determination of urea, electrolytes were used. Micral-test strips were used on samples negative only for albumin after using urine dipstick. Color comparison was done with the standardized color scale on test strip container after 5 minutes. Results: Fifty term newborn babies were enrolled, their serum electrolytes, creatinine and creatinine clearance were essentially normal. Six (12%) babies had positive microalbuminuria, while 44(88%) had negative microalbuminuria with specificity and negative predictive values of 100% and 88% respectively. Conclusion: Microalbuminuria was not useful for early detection of acute renal failure in babies with severe birth asphyxia, but further studies are recommended.